A novel subset of anti-inflammatory CD138(+) macrophages is deficient in mice with experimental lupus* - Han, Shuhong (J Immunol, 2017)
Dead cells accumulating in the tissues may contribute to chronic inflammation. We examined the cause of impaired apoptotic cell clearance human and murine lupus. Dead cells accumulated in bone marrow from lupus patients but not from non-autoimmune patients undergoing myeloablation, where they were efficiently removed by macrophages. Impaired apoptotic cell uptake by macrophages also was seen in mice treated i.p. with pristane (develop lupus) but not mineral oil (MO, do not develop lupus). The inflammatory response to both pristane and MO rapidly depleted resident (Tim4(+)) large peritoneal macrophages (LPM). The peritoneal exudate of pristane-treated mice contained mainly Ly6C(hi) inflammatory monocytes, whereas in MO-treated mice, it consisted predominantly of a novel subset of highly phagocytic macrophages resembling small peritoneal macrophages (SPM) that expressed CD138(+) and the scavenger receptor Marco. Treatment with anti-Marco neutralizing antibodies and the class A scavenger receptor antagonist polyinosinic acid inhibited phagocytosis of apoptotic cells by CD138(+) macrophages. CD138(+) macrophages expressed IL-10 receptor, CD206, and CCR2 but little TNFα or CX3CR1. They also expressed high levels of activated CREB, a transcription factor implicated in generating alternatively activated macrophages. Similar cells were identified in the spleen and lung of MO-treated mice and also were induced by lipopolysaccharide. We conclude that highly phagocytic, CD138(+) SPM-like cells with an anti-inflammatory phenotype may promote the resolution of inflammation in lupus and infectious diseases. These SPM-like cells are not restricted to the peritoneum, and may help clear apoptotic cells from tissues such as the lung, helping to prevent chronic inflammation.